Comparison of midupper arm circumference and weight-for-height z score for assessing acute malnutrition in children aged 6-60 months: an analytical study - Mehta, Nirali; Bhatt, R. G.; Vora, Hetal; Parmar, Bharat (International Journal of Contemporary Pediatrics, 2019)
Background: In clinical settings, wasting in childhood has primarily been assessed with the use of a weight-for-height z score (WHZ), and in community settings, it has been assessed via the mid upper arm circumference (MUAC) with a cutoff <115mm for severe wasting and 115-125mm for moderate wasting. Our recent experience indicates that many wasted children were not identified when these cutoffs for MUAC were used. Methods: Authors determined the cutoffs for MUAC to detect wasting in Indian children aged 6-60 mo. A secondary analysis was carried out on data from 1446 children aged 6-59 mo. The area under the receiver operating curve was used to indicate the most appropriate choice for cutoffs that related MUAC with WHZ. The MUAC measurement of each subject was taken using standard technique. Following the World Health Organization (WHO) age and sex-specific cut-off points, nutritional status of children was determined. Results: The mean±SD age for the entire group was 19.8±13.6 mo, MUAC was 132±13mm, and 45% of subjects were girls. Age-stratified analyses revealed that, for ages 6-24 mo, MUAC cutoffs were <120mm for a WHZ <-3 and <125mm for a WHZ <-2 with a sensitivity of 68.3% and 64.7%, respectively, and a specificity of 82.6% and 83.4%, respectively; for ages 25-60 mo, MUAC cutoffs were <135mm for a WHZ <-3 and <140mm for a WHZ <-2 with a sensitivity of 63.7% and 65.4%, respectively, and a specificity of 81.6% and 78.3%, respectively. Conclusions: The respective cutoffs for MUAC to better capture the vulnerability and risk of severe (WHZ <-3) and moderate (WHZ <-2) wasting would be <120 and <125mm for ages 6-24 mo, <135 and <140mm for ages 37-60 mo.